Formulation of methods for solving uniform future series and present and future gradient series: a practical approach in economic engineering - Contreras-González, Rosa Yaneth; Español, Español (AiBi Journal of Research, Administration and Engineering, 2025)
The article presents the design and validation of three engineering economics equations, in order to calculate uniform and gradient series for both present and future. The equations are designed to solve basic and complex practical situations such as annuity interruption. The research begins with a thorough review of engineering economics equations applied by different authors, as well as the importance of applying them in real contexts. Subsequently, a rigorous comparative analysis is carried out, which demonstrates that the equations proposed here offer greater understanding and effectiveness in responses than traditional equations, taking into account different contexts and situations with respect to annualities. In addition, research is conducted in a real environment, where several students from two different academic periods investigate different academic sources on economic engineering equations, solve practical exercises with the equation they found, then solve the same exercises with the equation under study, and compare the results with the conventional formula and the one that was designed, validating through a survey its practical utility. The results show that the conceptual simplicity of the proposed equations significantly improves the understanding, analysis and applicability in solving economic problems in the real environment. In this way it constitutes an important contribution to financial decision-making in personal and professional engineering or related areas.